2015
DOI: 10.1097/scs.0000000000001339
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate for Acute Traumatic Brain Injury

Abstract: The present meta-analysis of existing randomized controlled trials does not identify a significant beneficial effect in the mortality of traumatic brain injury patients; however, it suggests that magnesium sulfate shows a tendency to improve the Glasgow Outcome Scale and Glasgow Coma Scale scores, which is a promising result for traumatic brain injury therapy. Further effort is necessary to explore which subgroup of traumatic brain injury patients could benefit from magnesium sulfate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…A Cochrane systematic review including three randomized controlled trials (RCTs) published in 2008, found no beneficial role for magnesium treatment in acute TBI patients in terms of improving neurological outcomes or mortality and therefore did not support its use [ 42 ]. Another methodical review of the use of magnesium sulfate in acute TBI management, including eight RCTs published in 2015, also found no significant improvement in mortality but did report a nonsignificant improvement in GOS and GCS scores with magnesium therapy [ 43 ].…”
Section: Excitotoxicitymentioning
confidence: 99%
“…A Cochrane systematic review including three randomized controlled trials (RCTs) published in 2008, found no beneficial role for magnesium treatment in acute TBI patients in terms of improving neurological outcomes or mortality and therefore did not support its use [ 42 ]. Another methodical review of the use of magnesium sulfate in acute TBI management, including eight RCTs published in 2015, also found no significant improvement in mortality but did report a nonsignificant improvement in GOS and GCS scores with magnesium therapy [ 43 ].…”
Section: Excitotoxicitymentioning
confidence: 99%
“…A number of other experimental compounds have been successfully used to reduce edema formation in experimental TBI studies, including more recently progesterone and magnesium (4, 82), both of which have been unsuccessful in clinical trials to date (83, 84). Notably, when tested in our sheep model of TBI, our preliminary results also showed that both compounds had little effect on ICP or P bt O 2 after TBI (unpublished results).…”
Section: Icp and Brain Oxygenation After Tbimentioning
confidence: 99%
“…It interrupts a number of secondary factors involved in pathophysiology of TBI, the principal action that has been suggested by animal models is by NMDA receptor blockade and decreasing glutamate release. The other neuroprotective mechanisms proposed are improvement of cerebral blood flow, calcium channel blockage and inhibition of apoptosis [15, 31, 32]. A recent meta-analysis of existing randomized controlled trials did not identify a significant beneficial effect in the mortality of traumatic brain injury patients; however, it suggests that magnesium sulfate shows a tendency to improve the GOS and GCS scores, which is a promising result for traumatic brain injury therapy [33].…”
Section: Discussionmentioning
confidence: 99%